Meteorite terrestrial ages in Oman based on gamma spectrometry and sediment dating, focusing on the Ramlat Fasad dense collection area. (4th November 2021) - Rosén, Åke V.; Hofmann, Beda A.; Preusser, Frank; Gnos, Edwin; Eggenberger, Urs; Schumann, Marc; Szidat, Sönke
Abstract: We combine the search for young meteorites in the Omani‐Swiss collection (˜1140 fall events collected 2001–2018) using 22 Na and 44 Ti with luminescence and 14 C sediment ages from the Ramlat Fasad (RaF) dense collection area (DCA) of Oman to obtain combined terrestrial ages and maximum accumulation times, and test whether the proportion of young meteorites is consistent with the models of meteorite flux and weathering. Gamma‐ray spectrometry data for 22 Na show that two (0.17%) of the meteorites in the collection fell during the 20 yr preceding this study, consistent with the rates of meteorite accumulation. In the RaF DCA, meteorites are found on Quaternary to Neogene sediments, providing constraints for their maximum terrestrial ages. 44 Ti activities of the RaF 032 L6 strewn field found on deflated parts of active dunes indicate an age of 0.2–0.3 ka while dune sand optically stimulated luminescence ages constrain an upper age of 1.6 ka. Extensive sediment dating using luminescence methods in the RaF DCA area showed that all other meteorite finds were made on significantly older sediments (>10 ka). Dense accumulations of meteorites in RaF are found on blowouts of the Pliocene Marsawdad formation. Our combined results show that the proportion of meteorites with low terrestrial ages is low compared to other find areas, consistent with the previously determined high average terrestrial age Oman meteorites and significantly older than suggested by models of exponential decay. Oman meteorites may commonly have been buried within dunes and soils over extended periods, acting as a temporary protection against erosion.